Sustainable innovation in the metaverse: Blockchain's role in new business models - Le Bei Sze; Jari Salo; Teck Ming Tan (Digital Business, 2024)
This research aims to bridge a gap in the existing literature by investigating the role of the blockchain-based metaverse in fostering decentralized sustainable management, leveraging the principles of stakeholder capitalism theory. By conducting a content analysis of thirty-two expert reports from the blockchain-based metaverse industry, the study identifies five key attributes that can potentially cultivate innovation and decentralized sustainable management within the business domain. These attributes include a creator economy, a persistent synchronous virtual environment, decentralization, an interoperable network, and a digitalized mindset. The research underscores the need for stakeholders to adopt a sustainable approach when navigating the blockchain-based metaverse, highlighting the potential benefits achievable in a decentralized, hybrid physical-digital environment. This work stands as a pioneering effort in conceptualizing a theoretical framework that encapsulates decentralized sustainable management within the blockchain-based metaverse, underpinned by the principles of stakeholder capitalism. Thus, it contributes significantly to the academic discourse on the sustainable implications of blockchain technology in new business models.
Keywords: 650; Blockchain; Business model; Decentralization; Stakeholder capitalism; Sustainable management